Changing conceptions of historical thinking in History education: an Australian case study - Parkes, Robert J.; Donnelly, Debra (Revista Tempo e Argumento, 2014)
Many nations have experienced conflict over the content of their History curriculum, and debates over the relative importance of skills (historical thinking) versus content (historical knowledge). Australia is no exception. This paper seeks to contribute to discussions over the importance of historical thinking in History education by exploring the changing conceptions of historical thinking in the History curricula of New South Wales (NSW) (Australia’s most populous state; which evolved from the earliest British colony; has an uninterrupted tradition of History teaching in high schools; and a rather unique post-compulsory extension course). Recently, History has become a mandatory subject in all Australian schools from the foundation year through to the last year of compulsory schooling [F-10], for the first time since the federation of the Australian states (1901), when curriculum was constitutionally determined to be a State responsibility. This paper charts the changing forms and relative importance of historical thinking as an explicit outcome of History education in NSW History curricula, from its emergence in the 1970s elective History curriculum to current explication in the NSW syllabi for the mandatory Australian 'national' Curriculum. It also explores the nature and significance of the post-compulsory 'senior' History extension course in NSW, an option for History students in the final non-compulsory year of schooling. This extension course boldly incorporates the study of historiography, requiring students to apply their meta-historical insights in an original historiographic investigation, anchoring complex historical theory in an experience of being an historian. We argue that the move to incorporate historiography into the curriculum expands the notion of what constitutes historical thinking in History education. Thus, we conclude by reflecting on what these different ways of conceptualising historical thinking mean for the social and educational function of history, and what implications they suggest for History education. Keywords: History Teaching; Historical Thinking; Australian.